Regional Autonomic Contribution in Encouraging MSMEs Growth in City of Kediri, East Java, Indonesia - Marwanto, I Gusti Gede Heru (American Journal of Social Sciences and Humanities, 2019)
Regional autonomy has an important role in terms of providing local policies and regulations on the sustainability of the MSMEs sector. The existence of regional policies through good decentralization will provide progress for the people's economy. In the last 10 years since 2009-2019, several studies conducted in Kediri City as one of the regions of regional autonomy showed that most of the problems that arose in an effort to empower MSMEs from 4 main aspects namely, 1) internal MSMEs risk problems, 2) the risk of uncertainty or business climate, and 3) dependence on natural resources, and 4) the role of local government. To better understand the root causes and contribute to problem solving through strategy management, researchers use literature studies. Literature studies are expected to provide a clear picture of this. The results revealed that the contribution of regional autonomy in encouraging the growth of MSMEs can be done through 6 strategic indicators namely business capital, business climate, business protection, training and the establishment of special institutions, promotion and the economy is 'green'.